ANALYSIS COMOVEMENT OF THE JAKARTA ISLAMIC INDEX (JII) SHARIA STOCK AGAINST THE RUPIAH EXCHANGE RATE DURING THE COVID-19 PANDEMIC USING THE WAVELET COHERENCE METHOD - Rahmawati, Alfina
Econophysics is a field of science that implements and offers ideas, methods, and models on physics and complexity to analyze various economic data. In the financial market, investment is an indicator used in making decisions by investors when investing in order to minimize investment risk. Comovement is an asset price phenomenon that moves along with other asset prices. During the Covid-19 pandemic, there was a significant weakening of the rupiah exchange rate, the rupiah weakened to Rp16,575.00 per USD on March 23, 2020 and continued until early April 2020 where the rupiah exchange rate reached its lowest level. historically Rp16,741.00 per USD on April 2, 2020. The weakening of the rupiah exchange rate was also followed by a decline in the stock price index. One of the methods to analyze comovement is wavelet analysis with wavelet transform coherence which can be used to analyze the time domain as well as the frequency domain. In this study, a comovement analysis was carried out between the rupiah exchange rate and the Jakarta Islamic Index (JII) sharia stock price index. This study aims to determine the pattern of volatility and comovement as well as to determine an investment strategy based on the performance of JII Syariah shares during the period December 2019 until January 2022 using daily data. The data is processed using MATLAB software. Based on the results of the research, the JII Sharia shares studied were categorized into high and low commitments to the rupiah exchange rate. The analysis obtained is used to determine strategies for investors in making investments. Stocks with high commitment are for aggressive investors, moderate investments are for moderate investors, and low investments are for conservative investors.